2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609520
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic octacalcium phosphate: A possible carrier for mesenchymal stem cells in bone regeneration

Abstract: The present paper reviews biomaterial studies of synthetic octacalcium phosphate (OCP) as a scaffold of osteoblastic cells. OCP crystals have been suggested to be one of precursor phases in hydroxyapatite (HA) crystal formation in bone and tooth. The recent intensive biomaterials and tissue engineering studies using synthetic OCP disclosed the potential function of OCP as a bioactive material as well as synthetic HA materials due to its highly osteoconductive and biodegradable properties. In vitro studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that OCP coatings remarkably enhanced cell proliferation and ALP activity of MC3T3-E1 cells [64][65][66] . Therefore, it was suggested that OCP could control the environment during the conversion to HA under physiological conditions, which increased biological activity and bone regeneration enhancement 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that OCP coatings remarkably enhanced cell proliferation and ALP activity of MC3T3-E1 cells [64][65][66] . Therefore, it was suggested that OCP could control the environment during the conversion to HA under physiological conditions, which increased biological activity and bone regeneration enhancement 22 .…”
Section: Discussionmentioning
confidence: 99%